Caractéristiques rythmiques du chant de l'indri et nouvelles perspectives pour une évaluation comparative du rythme chez les primates non humains - Marco Gamba; Valeria Torti; Chiara De Gregorio; Teresa Raimondi; Longondraza Miaretsoa; Filippo Carugati; Walter Cristiano; Rose M. Randrianarison; Giovanna Bonadonna; Anna Zanoli; Olivier Friard; Daria Valente; et al. (Revue de Primatologie)
Since the discovery that rhythmic abilities are universal in humans, temporal features of vocal communication have greatly interested researchers studying animal communication. Rhythmic patterns are a valuable tool for species discrimination, mate choice, and individual recognition. A recent study showed that bird songs and human music share rhythmic categories when a signal's temporal intervals are distributed categorically rather than uniformly. Following that study, we aimed to investigate whether songs of indris (Indri indri), the only singing lemur, may show similar features. We measured the inter-onset intervals (tk), delimited by the onsets of two consecutive units, and the rhythmic ratios between these intervals (rk), calculated by dividing an interval by itself plus its adjacent, and finded a three-cluster distribution. Two clusters corresponded to rhythmic categories at 1:1 and 1:2, and the third approached a 2:1 ratio. Our results demonstrated for the first time that another primate besides humans produces categorical rhythms, an ability likely evolved convergently among singing species such as songbirds, indris, and humans. Understanding which communicative features are shared with other species is fundamental to understanding how they have evolved. In this regard, thanks to the simplicity of data processing and interpretation, our study relied on an accessible analytical approach that could open up new branches of the investigation into primate communication, leading the way to reconstruct a phylogeny of rhythm abilities across the entire order.